Spectrum of Gastroenteropancreatic NENs in Routine Histological Examinations of Bioptic and Surgical Specimen: A Study of 161 Cases Collected from 17 Departments of Pathology in the Czech Republic - Václav Mandys; Tomáš Jirásek (Gastroenterology Research and Practice)
Objective. To characterize GEP-NENs in routine biopsies and surgical specimen in the Czech Republic and to evaluate how WHO Classification (2010) is acceptable in diagnostic practice. Methods. Paraffin-embedded blocks and bioptic reports were collected from 17 departments of pathology. Histologic slides were stained with H&E and immunohistologically for CgA, synaptophysin, and Ki-67. Results. Out of 28 gastric NENs, there were 22 NETs, G1, 5 NETs, G2, and 1 NEC. Ten duodenal NENs were NETs, G1. Among 27 NENs of jejunum and ileum, 23 were NETs, G1, 2 NETs, G2, and 1 NEC and 1 mixed adenoneuroendocrine carcinoma (MANEC). Among 42 appendiceal “incidentalomas”, 39 were NETs G1, 2 goblet cell carcinoids, and 1 MANEC. Out of 34 large intestinal NENs, 30 were NETs, G1, 3 NETs, G2, and 1 NEC. One small intestinal and 6 large bowel neoplasms were reclassified as poorly differentiated adenocarcinomas. In 12 pancreatic NENs, there were 7 NETs, G1, 3 NETs, G2, and 2 NECs. Conclusions. Our study demonstrates differences in GEP-NENs frequency in sites of origin in our region, comparing to other countries. Regarding routine bioptic diagnostics, we gave evidence that the WHO 2010 classification of NENs is fully acceptable for exact categorisation of tumours.